Investigation on Viscoelastic-Creep Behavior of the Phase-Field Crystal Method - J Em-Udom; N Pisutha-Arnond (My University, 2018)
The phase-field crystal (PFC) method is a promising computational model with atomistic resolution and diffusive time-scale. In this study, we investigated the viscoelastic-creep behavior exhibited by the PFC model. We considered a one-dimensional crystal subjected to step changes in pressure and studied the time-dependent strain response from the system. The parametric study shows that the PFC model predicts the materials with higher density to exhibit higher stiffness and lower damping capacity while an increase in temperature results in lower stiffness and damping capacity. These predictions agree with experimental observations and show promising capability of the PFC method to model viscoelastic phenomena.
Keywords: Crystal (programming language); Solidification and crystal growth phenomena